Pleurotus tolimensis (Agaricales, Basidiomycota) a new species from a Tropical Dry Forest in Colombia, Tolima - Dávila-Giraldo, Lina R.; Zambrano-Forero, Cristian J.; Herrera-Sánchez, María P.; Rondón-Barragán, Iang S.; Murillo‑Arango, Walter; Motato-Vásquez, Viviana (Phytotaxa, 2025)
Pleurotus tolimensis is described as a novel species discovered in an urban remnant of Tropical Dry Forest in Tolima, Colombia. Species delimitation was supported by a combination of macro- and micromorphological characters, as well as multilocus phylogenetic analysis. Phylogenetic analyses based on a combined dataset comprising the internal transcribed spacer (ITS), the large subunit of the nuclear ribosomal RNA gene (28S), the translation elongation factor 1-α gene (TEF) and the largest and second largest subunits for the RNA polymerase genes (RPB1, RPB2). Phylogenetic analyses were inferred in a maximum likelihood and Bayesian inference framework. The results allowing the placement of P. tolimensis as a distinct lineage within the genus Pleurotus, closely related to P. floridanus. Diagnostic features include a light orange pileus with grayish edges, mucronate pleurocystidia, larger basidiospores, and the presence of rhomboid crystals near the hymenium, also present in culture. This study not only clarifies the taxonomy of Colombian Pleurotus but also highlights the high but still underexplored fungal diversity of the critically endangered Tropical Dry Forest. By contributing to reducing the Linnaean biodiversity shortfall, these findings provide essential baselines for future ecological, conservation, and applied research on Neotropical funga.